2015
DOI: 10.1063/1.4921151
|View full text |Cite
|
Sign up to set email alerts
|

Near-vacuum hohlraums for driving fusion implosions with high density carbon ablatorsa)

Abstract: Recent experiments at the National Ignition Facility [M. J. Edwards et al., Phys. Plasmas 20, 070501 (2013)] have explored driving high-density carbon ablators with near-vacuum hohlraums, which use a minimal amount of helium gas fill. These hohlraums show improved efficiency relative to conventional gas-filled hohlraums in terms of minimal backscatter, minimal generation of suprathermal electrons, and increased hohlraum-capsule coupling. Given these advantages, near-vacuum hohlraums are a promising choice for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…One approach to mitigating this is known as dynamic beam phasing, wherein the late "pole-hot" drive is compensated for by an earlier "waist-hot" radiation flux in order to obtain a round hot spot at peak compression. 17 However, recent work has shown that radiation flux symmetry swings can degrade performance (even if the hot spot is round at the time of peak emission) due to deviation between the hot spot core shape and the fuel areal density at peak compression, which results in poorly stagnating implosions (residual kinetic energy). 10 An alternative mitigation strategy is to provide more room for inner beam propagation by increasing the case-tocapsule ratio (CCR).…”
Section: Introductionmentioning
confidence: 99%
“…One approach to mitigating this is known as dynamic beam phasing, wherein the late "pole-hot" drive is compensated for by an earlier "waist-hot" radiation flux in order to obtain a round hot spot at peak compression. 17 However, recent work has shown that radiation flux symmetry swings can degrade performance (even if the hot spot is round at the time of peak emission) due to deviation between the hot spot core shape and the fuel areal density at peak compression, which results in poorly stagnating implosions (residual kinetic energy). 10 An alternative mitigation strategy is to provide more room for inner beam propagation by increasing the case-tocapsule ratio (CCR).…”
Section: Introductionmentioning
confidence: 99%
“…This method, called dynamic beam phasing, is described in more detail in a paper by Berzak Hopkins. 20 The inner-cone fraction for the first 2.5 ns of N130920 is indeed 20%, an inner:outer balance of 1:4.…”
Section: Model Adjustmentsmentioning
confidence: 91%
“…Recent experiments on the NIF in near-vacuum hohlraums have typically resulted in more prolate ("sausage") implosions than predicted by HYDRA. 20 The basic physics of symmetry control for vacuum hohlraums is essentially the same as for more conventional gas-filled hohlraums. The NIF laser beams are grouped into an inner cone with polar angles of 23.5 and 30 relative to the hohlraum axis and an outer cone with polar angles of 44.5 and 50 relative to the hohlraum axis.…”
Section: Model Adjustmentsmentioning
confidence: 99%
See 2 more Smart Citations